Estudo experimental da aplicação de ranhuras longitudinais em escoamentos turbulentos internos - Norões, Higuel Parga de Paiva (2018)
Drag reduction techniques are used for energy consumption reduction in various engineering transport systems. Among them, longitudinal riblets stand out since they are passive and of relative easy fabrication when compared to other techniques. It is shown on literature that longitudinal riblets act on modifying turbulent boundary layer of both internal and external flows. Change on flow dynamics near the wall leads to a decrease of up to to 10% in shear stress, which directly reflects system’s energy consumption reduction. The built and analysed experiment of this work consists in comparing the internal flow of a smooth wall rectangular channel and a longitudinal riblets covered channel. Riblets dimensions are optimal as pre-established by literature. Measurements techniques of pressure variation, particle image velocimetry and laser Doppler anemometry. Results show drag reductions of up to 20%, consistent between independent measurement techniques. The achievement of this unprecedented outcome shows the use of longitudinal riblets can and must be studied in-depth for successful application in industry.